Gas Wars: Retail Gasoline Price Fluctuations - Castanias, Rick; Johnson, Herb (The Review of Economics and Statistics, 1993)
This paper examines the retail gasoline price fluctuations known as gas wars. Weekly prices for the Los Angeles area were examined for the period from January 2, 1968 through December 23, 1975. The observed fluctuations were remarkably regular and, apparently, large ly predictable. The data appear consistent with the recent game theory model of E. Maskin and J. Tirole in which competing firms produce Edgeworth cycles by undercutting each other and eventually relenting. Copyright 1993 by MIT Press.